Role Games as a Learning Method - Djabbarova, D. (Researchparks Publishing, 2023)
In article are considered problems of using the role-playing games in educational process, are shown ways and means of their overcoming, is proved efficiency of the given methodical way for development of students’ abilities for independent creative thinking, decision-making on workplace issues and situations, reasoned expression of the ideas, fast adaptation and work modeling in the team.